Existential Psychotherapy Supervision: The Supervisor's Perspective. (May 2022) - Silva, Sara; Sousa, Daniel
Supervision is a cross-disciplinary practice among various professional groups. This study focuses on clinical supervision as a practice linked to psychology and psychotherapy. The literature highlights the need to expand and consolidate knowledge in this area. Specifically, in the few existing approaches to research on existential supervision, the need for the systematization of knowledge is clear. The use of qualitative methods is recognized as an approach that is likely to enrich knowledge of supervision.Objective: The aim of this study was to explore the theme of clinical supervision, particularly as it relates to existential psychotherapy, from the supervisor's perspective to assess insights from the experience of each participant.Method: The three participants are both existential psychotherapists and supervisors that apply the same approach, in group mode, in the context of psychotherapist training. The data were collected using phenomenological interviews. A comprehensive analysis of the transcripts of the interviews was performed using the phenomenological method.Results: Emerging themes presented a general meaning structure that represents eidetic dimensions and how they are related. The eidetic dimensions, relationship and responsiveness, arise in the existential approach as the foundational and promotional aspects of successful supervision.